2021
DOI: 10.1051/e3sconf/202131207001
|View full text |Cite
|
Sign up to set email alerts
|

3D CFD simulation of a gaseous fuel injection in a hydrogen-fueled internal combustion engine

Abstract: Nowadays, one of the hottest topic in the automotive engineering community is the reduction of fossil fuels. Hydrogen is an alternative energy source that is already providing clean, renewable, and efficient power being used in fuel cells. Despite being developed since a few decades, fuel cells are affected by several hurdles, the most impacting one being their cost per unit power. While waiting for their cost reduction and mass-market penetration, hydrogen-fueled internal combustion engines (H2ICEs) can be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Schlieren measurements confirmed that improvements in the agreement between numerical and experimental results can be achieved with an extended duration of the injection ramp during the earlier transient stage of the injection. The lower fuel concentrations observed in the simulations might be therefore, due to the anticipated reduction of the injected mass, as portrayed by Barbato in [14]. On the other hand, these authors suggest that, for early injection, the transient duration only marginally affects the mixture formation process occurring during the rest of the compression stroke.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Schlieren measurements confirmed that improvements in the agreement between numerical and experimental results can be achieved with an extended duration of the injection ramp during the earlier transient stage of the injection. The lower fuel concentrations observed in the simulations might be therefore, due to the anticipated reduction of the injected mass, as portrayed by Barbato in [14]. On the other hand, these authors suggest that, for early injection, the transient duration only marginally affects the mixture formation process occurring during the rest of the compression stroke.…”
Section: Resultsmentioning
confidence: 77%
“…Given the H2 mass flow rate profile experimentally determined (see Figure 3) and the injection surface area, the hydrogen mass-flow rate through the stable injection has been calculated and set equal to 2.381 g/s in order to achieve the target of 4.365 mg of hydrogen injected per-cycle. Previous numerical activities performed on the Sandia engine case studies have executed timestepsensitivity analysis resulting in a negligible impact over the overall computational solution on mixture formation [14]. Therefore, for the current activity a time discretization of 0.5°CA and 0.1°CA had been employed respectively for the gas exchange and for the injection simulations.…”
Section: Numerical Setupmentioning
confidence: 99%